PENGARUH SELF CONTROL DAN STRES KERJA TERHADAP PERILAKU CYBERLOAFING DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI PADA PT. ASURANSI JASINDO CABANG MEDAN - Juanda, M Bayu; Sabrina, R; Effendi, Sjahril (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to determine and analyze the effect of self-control and job stress on cyberloafing behavior moderated by organizational commitment at PT Asuransi Jasindo Medan Branch Office. The sample of this study amounted to 40 employees, which will be analyzed using SEM-PLS statistical analysis. This study proves that self-control negatively and significantly affects cyberloafing behavior. Job stress positively and significantly affects cyberloafing behavior. Organizational commitment does not moderate the effect of self control on cyberloafing behavior. Organizational commitment does not moderate the effect of job stress on cyberloafing behavior.